The Prognostic Value Of Apelin On Cardiac Outcomes In Patients With Chronic Kidney Disease And The Relationship With Genetic Polymorphism Of Apelin - علي جانيت; محمد عماد خياط; عبد الفتاح عباس (Latakia University Journal -Medical Sciences Series, 2024)
Introduction: Cardiovascular disease is a common complication of chronic renal failure, especially in its end stages. It is also the main cause of death in patients with chronic renal disease, as it is responsible for 50% of all deaths. Recently, the role of apelin, which is an endogenous peptide coded by the APLN gene and serves in the pathophysiology of cardiac failure, has been defined. Apelin also appeared to be in lower levels in CKD patients. Thus the purpose of this study is to examine the prognostic role of apelin as an early marker of CVD in the context of CKD and studying the genetic polymorphism of apelin. Methods: The sample was taken from the Department of Nephrology of Tishreen University’s Hospital, consisting of 70 subjects suffering from CKD specifically stage 2-4. They were divided based on their glomerular filtration rate (GFR), in addition to that 15 other nephrologically and cardiovascualrly healthy subjects were added as a control group. The control group is homogenous in terms of age and sex with the test subjects. The sample’s subjects were monitored for 18 months starting on the 25th of July 2021 and ending on the 12th of December 2022. Their cardiovascular status was observed consistently by the hospital’s cardiologists in addition to their kidney and overall status through a weekly patient examination. Results: As anticipated, the average GFR of the observation subjects was lower than those of the control group. Which was 42.06 ml/min/1.73 m^2 compared to 122.4 and this difference carried a big statistical significance being of p<0.0001. Also we found that the average apelin was lower in CKD patients than in the control group, being 378.86 compared to 663.93, carrying statistical signicance of p<0.0001. Additionally, the average systolic and diastolic blood pressures were higher in CKD patients than the control group. All members of the control group were from the TT genetic type while 95% of the chronic renal disease patients having the TT genetic type and this difference was not statistically important; The cardiovascular complications were more present in CKD patients than in the control group, having 39% prevalence in comparison to the latter. This difference is also statistically significant p=0.017. Myocardial infarction and left ventricular hypertrophy were the most commonly occurring complications amongst CKD patients. Conclusion: We found that only apelin had a statistically significant importance in the incidence of CVD in CKD patients. As apelin levels were negatively correlated with the known CVD risk factors and positively correlated with eGFR. These findings solidify the role of apelin as a prognostic marker for the progression of CVDs in CKD patients.